The stranger at the wedding : a novel - Gauntlett, A. E. (Henry Holt and Company, 2024)
"Before love at first sight, there were things no one saw. Annie never much believed in love. That is, until meeting Mark. After crossing paths on morning commutes, they connect at a group counseling session for trauma survivors. Each recognizes something in the other, though both hide their own troubled pasts. It's a whirlwind romance that propels Annie through their courtship, all the way to her wedding day-a day she couldn't have predicted for herself once upon a time yet now feels surer about than anything in her life. But as Annie stands at the altar, casting her eyes over the rows of well-wishers, she spots a stranger in the crowd, and she soon learns that her new life isn't going to be the happily ever after that she had planned. Who is the stranger at the wedding? What really happened to Mark's first wife? And was Annie and Mark's meeting as random as it first appeared, or is something more sinister at work? A sizzling thriller, The Stranger at the Wedding will make you think twice before saying "I do.""--